The Rise of Fintech and its Impact on Credit Risk - Dr O.P. Singh (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2024)
Fintech companies are using technology to disrupt the traditional financial services industry. This includes the development of new credit scoring models and lending platforms. This paper will explore how fintech is changing the credit risk landscape, and the potential benefits and challenges for borrowers and lenders alike. It will also discuss the regulatory challenges associated with the growth of fintech.